1998
DOI: 10.1021/ef9701450
|View full text |Cite
|
Sign up to set email alerts
|

Structural Uniformity of Toluene-Insolubles from Heat-Treated Coal Tar Pitch As Determined by Solid State13C NMR Spectroscopy

Abstract: A suite of coal tar pitches (CTPs) thermally treated to varying degrees and their tolueneinsoluble (TI) fractions have been characterized by solid state 13 C nuclear magnetic resonance (NMR). The nonprotonated aromatic carbon concentrations estimated from dipolar dephasing experiments using cross polarization with a relatively long contact time (5 ms) and the quantitatively reliable single-pulse excitation (SPE) technique were in good agreement and these concentrations were used to deduce the average ring size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Table lists the solid-state 13 C NMR data for the solid residue after stressing the DA/HT LCO and JP-8P jet fuels at 482 °C for 90 min. For both samples the quantitative single-pulse excitation technique was used, which has been proved to detect virtually all the carbon in carbonaceous systems as condensed as coal tar pitches and anthracites coals. , As discussed earlier, an aromaticity of 0.97 to 0.98 was observed for the solid residues from the stressed fuels (Table ). Further, the elemental analysis showed as expected that the heteroatomic content (oxygen, nitrogen, and sulfur) was less than 0.5 wt %.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Table lists the solid-state 13 C NMR data for the solid residue after stressing the DA/HT LCO and JP-8P jet fuels at 482 °C for 90 min. For both samples the quantitative single-pulse excitation technique was used, which has been proved to detect virtually all the carbon in carbonaceous systems as condensed as coal tar pitches and anthracites coals. , As discussed earlier, an aromaticity of 0.97 to 0.98 was observed for the solid residues from the stressed fuels (Table ). Further, the elemental analysis showed as expected that the heteroatomic content (oxygen, nitrogen, and sulfur) was less than 0.5 wt %.…”
Section: Resultsmentioning
confidence: 98%
“…Characterization of Solid Deposits. Figure shows the solid-state 13 C NMR spectrum of the solid residue formed from DA/HT LCO at 482 °C after 90 min using the quantitative single-pulse excitation (SPE) technique . Clearly, the spectrum is dominated by the aromatic peak centered at about 126 ppm and has spinning sidebands at 270 and −30 ppm that are out of the region of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the evaluation of aromaticity from the ratio of aromatic and aliphatic C–H stretching signals can be misleading, and the quantitative analysis of aliphatic and aromatic hydrogen is instead required. The quantitative analysis of aliphatic and aromatic hydrogen and carbon is generally carried out by sophisticated and time-consuming 1 H and 13 C NMR spectroscopy techniques. , A newly developed FTIR method, described in detail in a previous work, has been applied here for quantitatively determining the aliphatic and aromatic hydrogen contents for CP and NP. This quantitative FTIR method, briefly described in the following paragraph, has allowed for determining the weight percentages of aromatic and aliphatic hydrogen (in the form of methyl CH 3 , methylene CH 2 , and methyne CH groups) and, thereby, the evaluation of aliphatic and aromatic carbon.…”
Section: Resultsmentioning
confidence: 99%
“…The versatility of NMR spectroscopy allows a wide range of different pulse programs to be applied to examine specific aspects of coal and petroleum derived materials. Numerous reports in the literature have described NMR methods capable of investigating internal and peripheral structural features in complex molecules and their mixtures. …”
Section: Examining Higher Mass Fractions By Solution State 13c Nmrmentioning
confidence: 99%
“…Solid-state NMR often seems a useful analytical route for tackling heavy coal and petroleum derived fractions, as it avoids the need for a solvent. However, it is often found that the resolution of signal is not sufficiently high for identifying detailed structural differences between samples. ,, Moreover, instrument artifacts known as “spinning side bands” often overlap with signal from the reference material or aliphatic groups, introducing errors that are significant when it is intended to use the NMR data quantitatively. , The present review will focus on solution state NMR methods suitable for obtaining quantitative structural information on aromatic carbon and hydrogen content of complex hydrocarbon mixtures as well as on the proportions of the different types of aromatic and aliphatic groups.…”
Section: Examining Higher Mass Fractions By Solution State 13c Nmrmentioning
confidence: 99%